Synthesis of Novel Tetranorlabdane Derivatives with Unprecedented Carbon Skeleton - Ciocarlan, Alexandru; Aricu, Aculina; Lungu, Lidia; Edu, Carolina; Barba, Alic; Shova, Sergiu; Mangalagiu, Ionel I.; D’Ambrosio, Michele; Nicolescu, Alina; Deleanu, Calin; Vornicu, Nicoleta (Synlett, 2017)
Synthesis of novel tetranorlabdane derivatives including hybride with terpeno-(1,2)-diazine units and dimers with an unprecedented carbon skeleton, was performed based on methyl 7-oxo-13,14,15,16-tetranorlabd-8-en-12-oate intermediate. The structures of the synthesized compounds have been fully confirmed, including by X-ray diffraction, and their antifungal and antibacterial activity was tested. A possible mechanistic pathway of the cycloaddition reaction is considered.
Keywords: (–)-sclareol; (+)-sclareolide; methyl 7-oxo-13,14,15,16-tetranorlabd-8-en-12-oate; cycloaddition; dimer; terpeno-(1,2)-diazine